Global impact of trace non-essential heavy metal contaminants in industrial cannabis bioeconomy. (2nd October 2022) - Bengyella, Louis; Kuddus, Mohammed; Mukherjee, Piyali; Fonmboh, Dobgima J.; Kaminski, John E.
Abstract: The intrinsic signatures of Cannabis species to bioaccumulate non-essential harmful heavy metals (HMs) such as As, Pb, Cr, and Hg are determined by their high tolerance, weedy propensities, phenotypic plasticity attributes, and pedoclimatic stress adaptation in a biota. This unstructured meta-analysis study provides details of cannabi s involvement in HMs phytoremediation, new insights into HMs transportation and distribution, homeostasis, and health implications of HMs contaminated product. A blueprint of agronomic strategies to alleviate HMs uptake by cannabis is proposed. We show revamping cannabis global production necessitates a rethinking of agronomic best practices and post-harvest technologies to remove metal contaminants.